EFFECT OF BIOCHAR ON CONTENT AND UPTAKE OF MACRONUTRIENTS BY RABI GROUNDNUT (Arachis hypogaea L.) IN SANDY LOAM SOILS OF NORTH COASTAL ANDHRA PRADESH - B. GOWTHAMI, P. GURUMURTHY*, CH. SUJANI; M. SRIREKHA (The Journal of Research ANGRAU, 2019)
A field experiment was conducted to evaluate the effect of biochar on Rabi groundnut nutrition in red sandy loam soils. Eight treatments viz., control (T1), 100% RDF only (T2), 100% RDF + biochar @ 2 t ha-1 (T3), 100% RDF + biochar @ 4 t ha-1 (T4), 100% RDF + biochar @ 6 t ha-1 (T5), 75% RDF + biochar @ 2 t ha-1 (T6), 75% RDF + biochar @ 4 t ha-1 (T7) and 75% RDF + biochar @ 6 t ha-1 (T8) were laid out in RBD design replicated thrice. Soil application of biochar significantly increased the N, P2O5, K2O and Ca concentration in both groundnut haulms and pods, however, Mg and S contents slightly increased by biochar addition. Highest nitrogen content of 2.86% was observed in groundnut pods when biochar applied @ 6 t ha-1 along with 100% RDF (T5), which found statistically on par with other treatments except T6 and T1 in which the N was significantly lower than in T5. The N, P2O5 and K2O content were significantly high in all the treatments when compared to control (T1). Calcium content in groundnut haulm and pods was significantly higher in biochar applied treatments (T3, T4, T5, T6, T7 and T8) compared to no biochar applied treatments (T1 and T2). However, calcium content with the biochar application @ 6 t ha-1 (T5 and T8) was significantly higher when compared to treatments with biochar application @ 2 t ha-1 (T3 and T6). The total uptake of N, P2O5, K2O, Ca, Mg and S by groundnut crop was significantly influenced by biochar application in combination with 100% RDF (T5, T4,T3) or 75% RDF (T6, T7 & T8) and RDF alone (T2) when compared to control(T1). The increased nutrient uptake was found mainly due to enhanced groundnut haulm and pod yield.